The alteration of IL-17 signaling pathway in bipolar disorder: a preliminary study with transcriptomic perspective - Xiaobo Wang; Xiaobo Wang; Su Yu; Zhen Gao; Fangming Xu; Yumei Wang; Yumei Wang; Yumei Wang; Tianle Zhang; Tingting Xie; Xihua Jia (Frontiers in Psychiatry)
ObjectiveBipolar Disorder (BD) is a complex psychiatric condition influenced by genetic and environmental factors. This study aims to explore global mRNA expression in Peripheral blood white cells (PBMC) of BD patients.MethodsWe analyzed whole-genome gene expression profiles from PBMC of 12 BD states-manic (BD-M), 12 BD states-depressive (BD-D), and 12 matched healthy controls (HC) using microarrays. Validation of differentially expressed genes within the IL-17 pathway was conducted through qRT-PCR, while ELISA measured specific protein levels. GO and KEGG pathway enrichment analyses were performed, alongside PPI analysis and Gene Set Variation Analysis (GSVA) to assess immune cell infiltration.ResultsIn the comparison between BD and HC, a total of 304 differentially expressed genes (DEGs) were identified, of which 217 genes were upregulated and 87 genes were downregulated. In the comparisons between BD and HC, BD-M and HC, and BD-D and HC, 91 DEGs were found. Enrichment analysis suggested that biological processes and signaling pathways related to extracellular matrix, stress response, heparin binding, and immune inflammation were upregulated in the BD group. KEGG analysis and PPI results indicate that the IL-17 signaling pathway plays an important role in BD and its subtypes. In the IL-17 signaling pathway, compared to HC, the expression of Jun, Fosb, Fosl1, TNFAIP3, NFKBIA, CXCL2, CXCL8, IL6 and IL17 genes was upregulated in BD patients. RT-qPCR analysis showed that the expression of Jun, Fosb, Fosl1, NFKBIA, TNFAIP3, CXCL2, and CXCL8 genes was significantly upregulated in BD, ELISA results indicated that the protein levels of CXCL8/IL-8, IL-6 and IL-17 in the BD group were significantly higher than those in the HC group (all P < 0.05). Immune infiltration analysis showed that central memory CD4+ T cells (P=0.010), eosinophils (P=0.038), and mast cells (P=0.029) were increased in infiltration in the BD group.ConclusionThis study integrates transcriptomics and immune microenvironment analysis, suggesting that the IL-17 signaling pathway may be involved in the pathogenesis of BD and its subtypes through inflammation triggered by chemokines. This research deepens our understanding of the molecular mechanisms of BD and emphasizes the importance of the immune system in its pathology.